Quantitative proteomics reveals divergent responses in Apis mellifera worker and drone pupae to parasitization by Varroa destructor. (May 2018) - Surlis, Carla; Carolan, James C.; Coffey, Mary; Kavanagh, Kevin
Graphical abstract: Highlights: Varroa -parasitized pupae of Apis mellifera displayed reduced abundance in a range of proteins. Cytoskeletal and muscle proteins were at a higher abundance in Varroa - parasitized drone pupae. Proteins involved in metabolism were more abundant in Varroa parasitized worker pupae. A higher level of proteomic alteration is present in the Varroa - parasitized worker pupae. Abstract: Varroa destructor is a haemophagous ectoparasite of honeybees and is considered a major causal agent of colony losses in Europe and North America. Although originating in Eastern Asia where it parasitizes Apis cerana, it has shifted hosts to the western honeybee Apis mellifera on which it has a greater deleterious effect on the individual and colony level . To investigate this important host-parasite interaction and to determine whether Varroa causes different effects on different castes we conducted a label free quantitative proteomic analysis of Varroa- parasitized and non-parasitized drone and worker Apis mellifera pupae. 1195 proteins were identified in total, of which 202 and 250 were differentially abundant in parasitized drone and worker pupae, respectively. Both parasitized drone and worker pupae displayed reduced abundance in proteins associated with the cuticle, lipid transport and innate immunity. Proteins involved in metabolic processes were more abundant in both parasitized castes although the response in workers was more pronounced. A number of caste specific responses were observed including differential abundance of numerous cytoskeletal and muscle proteins, which were of higher abundance in parasitized drones in comparison to parasitized workers. Proteins involved in fatty acid and carbohydrate metabolism were more abundant in parasitized workers as were a large number of ribosomal proteins highlighting either potentially divergent responses to Varroa or a different strategy by the mite when parasitizing the different castes. This data improves our understanding of this interaction and may provide a basis for future studies into improvements to therapy and control of Varroasis.